Structural-and-phase states, crystallogeometric and crystallochemical parameters of membrane palladium-based alloys; Mechanical Engineering, Automation and Control Systems (MEACS) - Klopotov V. D. Vladimir Dmitrievich; Potekaev A. I. Alexandr; Kozyreva R. A. Rima; Markova T. N. Tatiana; Matunin A. N. Alexandr; Klopotov A. A. Anatoly (2015, 2015)
Title screen